1995
DOI: 10.1002/hyp.3360090205
|View full text |Cite
|
Sign up to set email alerts
|

Influence of sea salt on stream water chemistry in an upland afforested catchment

Abstract: The chemistry of bulk precipitation and stream water was monitored in an acidic afforested catchment at Llyn Brianne in upland Wales between 1985 and 1990. Throughfall, stemflow and soil water chemistry were also monitored between 1988 and 1989. Marine-derived solutes dominated the ionic composition of precipitation and stream water, which had mean C1 concentrations of 11 3 pequiv. 1-' and 245 pequiv. 1-', respectively. The higher concentrations in stream water reflect occult and dry deposition on the forest c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…This may suggest that Al 3+ levels and streamwater acidity can be exacerbated following such periods of high sea-salt deposition as observed elsewhere in the UK uplands (e.g. Langan, 1989;Soulsby, 1995b;Jarvie et al, 2001;Bridcut et al, 2004). Such studies have shown that Na concentrations enhance ion exchange reactions which displace Al 3+ from soil cation exchange sites which are then mobilized to surface waters with Cl as the accompanying anion (Soulsby and Reynolds, 1992).…”
Section: Time Seriesmentioning
confidence: 91%
“…This may suggest that Al 3+ levels and streamwater acidity can be exacerbated following such periods of high sea-salt deposition as observed elsewhere in the UK uplands (e.g. Langan, 1989;Soulsby, 1995b;Jarvie et al, 2001;Bridcut et al, 2004). Such studies have shown that Na concentrations enhance ion exchange reactions which displace Al 3+ from soil cation exchange sites which are then mobilized to surface waters with Cl as the accompanying anion (Soulsby and Reynolds, 1992).…”
Section: Time Seriesmentioning
confidence: 91%
“…Silicate weathering, considered to be the dominant process of weathering in the soils, is modified to a large degree by ion-exchange reactions involving H + and sea-salt inputs (Soulsby, 1995b). Inputs of many trace elements, including trace metals Sr and Ba, are important indicators of weathering reactions but the fine-grained nature of the host minerals makes it difficult to ascertain specific reactions.…”
Section: Spatial Variations In Chemical Weatheringmentioning
confidence: 99%
“…Deeper flow paths in the lower soils were considered to be an important influence on stream water chemistry. Soulsby (1995) identified storms where runoff generation was dominated by the displacement of 'old' pre-event water. These results were consistent with earlier work by Robson and Neal (1990) but the source of this pre-event water was thought to be in the deeper soil horizons (Robson et al, 1993).…”
Section: Introductionmentioning
confidence: 98%